Rancang Bangun Sensor Pergeseran Tanah Digital - Suryono, Suryono (BERKALA FISIKA, 2008)
The Research has been produced digital displacement field sensor system.  This system can be applied on displacement level monitoring of building, bridge, dike  and so forth. This developed system work serial digitally so that It can be connected to computer for many purpose. The field Displacement sensor use sliding potentiometer and  a 10 bit Analog to Digital Converter (ADC) at microcontroller. The value of field displacement is sent digitally as multi byte serial  data through UART serial communication protocol. The acquired data read to computer through COM1 with Borland Delphi 7.0 program. The research A system which can measure field displacement has been  acquired from this research. The system has 1 mm resolution specification with the range of measurement up to 57 meters. From the  sensor’s output  has been acquired the output of the system with has the equation  y = 0,990x + 0,154 with the linear correlation  0,998. Keyword : Displacement, digital, serial